Quantitative Ethnomedicinal study of the Flora of Tehsil Lahor, District Swabi, Khyber Pakhtunkhwa, Pakistan - Ali, Arshad; Jan, Gul; Irfan, Muhammad; Jan, Farzana Gul; Ullah, Fazal (Ethnobotany Research and Applications, 2023)
Introduction: The current study expresses the folk knowledge of medicinal plants of the Flora of tehsil Lahor, District Swabi, Khyber Pakhtunkhwa, Pakistan. The presenting study for the first time provides a deep sight into folk medicinal knowledge of the study area through quantitative analysis. Materials and Methods: The native knowledge of the medicinal plant has been documented with the help of the local people of the area through the interviews of the experts of the area and also used the questionnaire methods from January to December 2018. Results: A total of 100 plants taxa belonging to 87 genera and 50 families were documented. In our findings, the Poaceae was the leading family with 8 taxa each (16%), while the Asteraceae and Euphorbiaceae were considered as the second leading families with 7 taxa each (28%) followed by third Solanaceae having 6 taxa with (12%). Amongst them 2 taxa were Pteridophytes, and 98 taxa were Angiosperms. Habit wise 76 taxa were herbs, while 13 taxa were shrubs, and 11 taxa were trees. Regarding the parts used whole plants were utilized with 43% dominantly. Regarding the quantitative analysis, the RFC ranged from 0.80 for Peganum harmala to 0.05 for Cannabis sativa, UV ranged from 0.21 for Mentha longifolia to 0.03 for Ricinus communis, ICF ranged from 0.66 for whooping cough to 0.77 for diabetes, while the highest FL was found for Oxalis corniculata (91.8), followed by Fumaria indica (91), and Datura innoxia (90). The highest rank order priority (ROP) was reported for Otostegia limbata (212.8), followed by Lindenbergia indica (205.2). Conclusions: The diversity of medicinal plant taxa and their association with traditional knowledge has huge importance in primary healthcare systems. Most of the people in the study area were dependent on therapeutic taxa for the treatment of many disorders such as curing whooping cough, snake bite, anemia, psoriasis, and tooth decay. Keywords: Ethnomedicinal, Traditional, Lahor, Swabi, Pakistan.